Hydrogen Intensity and Real-Time Analysis Experiment: 256-element array status and overview - (:unkn) unknown (My University, 2022)
The Hydrogen Intensity and Real-time Analysis Experiment (HIRAX) is a radio interferometer array currently in development, with an initial 256-element array to be deployed at the South African Radio Astronomy Observatory Square Kilometer Array site in South Africa. Each of the 6 m, f  /  0.23 dishes will be instrumented with dual-polarization feeds operating over a frequency range of 400 to 800 MHz. Through intensity mapping of the 21 cm emission line of neutral hydrogen, HIRAX will provide a cosmological survey of the distribution of large-scale structure over the redshift range of 0.775  <  z  <  2.55 over ∼15,000 square degrees of the southern sky. The statistical power of such a survey is sufficient to produce ∼7  %   constraints on the dark energy equation of state parameter when combined with measurements from the Planck satellite. Additionally, HIRAX will provide a highly competitive platform for radio transient and HI absorber science while enabling a multitude of cross-correlation studies. We describe the science goals of the experiment, overview of the design and status of the subcomponents of the telescope system, and describe the expected performance of the initial 256-element array as well as the planned future expansion to the final, 1024-element array.
Keywords: African Research